2016
DOI: 10.1371/journal.pone.0156664
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Shell Colour Pigments in Marine Snails Clanculus pharaonius and C. margaritarius (Trochoidea; Gastropoda)

Abstract: Colour and pattern are key traits with important roles in camouflage, warning and attraction. Ideally, in order to begin to understand the evolution and ecology of colour in nature, it is important to identify and, where possible, fully characterise pigments using biochemical methods. The phylum Mollusca includes some of the most beautiful exemplars of biological pigmentation, with the vivid colours of sea shells particularly prized by collectors and scientists alike. Biochemical studies of molluscan shell col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 75 publications
2
60
1
1
Order By: Relevance
“…Protoporphyrin (a cyclic tetrapyrrole) is an immediate precursor of the heme molecule, whereas biliverdin (a linear tetrapyrrole) is a product of hemoglobin breakdown. Protoporphyrin and biliverdin pigments can bind ions of trace metals, primarily iron (Fe) or zinc (Zn), but almost all other metals can be incorporated into their molecules (Ostfeld and Tsutsui 1974, Mikšík et al 1996, Casini et al 2003, Williams et al 2016. Protoporphyrin and biliverdin occur at varying levels in the shells of most birds' eggs, irrespective of their coloration (Mikšík et al 1996, Cassey et al 2011, Wang et al 2011, Brulez et al 2016, and their distribution varies between the speckled and plain areas of the shells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protoporphyrin (a cyclic tetrapyrrole) is an immediate precursor of the heme molecule, whereas biliverdin (a linear tetrapyrrole) is a product of hemoglobin breakdown. Protoporphyrin and biliverdin pigments can bind ions of trace metals, primarily iron (Fe) or zinc (Zn), but almost all other metals can be incorporated into their molecules (Ostfeld and Tsutsui 1974, Mikšík et al 1996, Casini et al 2003, Williams et al 2016. Protoporphyrin and biliverdin occur at varying levels in the shells of most birds' eggs, irrespective of their coloration (Mikšík et al 1996, Cassey et al 2011, Wang et al 2011, Brulez et al 2016, and their distribution varies between the speckled and plain areas of the shells .…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation into the composition of pigments present in the shells of molluscs and birds' eggs revealed that protoporphyrin pigments occurred in both these evolutionarily distant groups of animals but that biliverdin was present only in birds' eggshells (Verdes et al 2015). Another recent investigation of molluscs showed that the more intensive dark pigmentation due to the presence of protoporphyrin increased the content of some trace elements (measured only by scanning electron microscope) like Cu (Williams et al 2016). We therefore hypothesize that an analogous relationship between the presence of protoporphyrin pigments and the content of macrominerals and microminerals (trace elements) should also apply to the maculation of birds' eggs, as suggested earlier by Mikšík et al (1996).…”
Section: Introductionmentioning
confidence: 99%
“… Specimen number, sampling locality, analyses undertaken in this study (red font) and in (Williams et al., ; black font). …”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from mantle edge tissue from specimens of two C. margaritarius, one C. pharaonius and one Ca. zizyphinum, and from colored tissue from the side of the foot of one specimen of C. margaritarius , which is also colored by porphyrins (Williams et al., ; Table ). RNA was extracted using the RNeasy Fibrous Tissue Mini Kit (Qiagen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation